Principle of Legality and the Rule of Law Enforcement Problems - Кучма, Ольга Леонідівна (Херсонський державний університет, 2015)
The article analyzes the principles of justice and rule of law, setting priorities in the application of law in the settlement of relations. Substantiated the thesis that the principle of legality is the first among the principles that makes it possible to implement all the other principles that are directly or indirectly enshrined in legislation, including the rule of law

Стаття присвячена аналізу принципів законності та верховенства права, визначенні пріоритетів у застосуванні законодавства при врегулюванні правовідносин. Обґрунтовується теза про те, що принцип законності є першим серед принципів, який робить можливим реалізацію всіх інших принципів, які прямо чи опосередковано закріплені у законодавстві, в тому числі і принципа верховенства права
Принципи законності й верховенства права: проблеми правозастосування
Keywords: принципи права; законність; верховенство права; правовий нігілізм; конституція; справедливий суд; principles of law; legality; rule of law; legal nihilism; constitution; fair trial